Examining equity in Ghana's national REDD+ process - Saeed, A; McDermott, C; Boyd, E (Elsevier, 2018)
Reducing Emissions from Deforestation and Forest Degradation, sustainable forest management, enhancement of forest carbon stocks and conservation (REDD+) aims to reduce the 12–17% of global greenhouse gas emissions attributable to forest loss worldwide. As tropical countries undertake REDD+ readiness, vital questions arise around the equity of REDD+ interventions. In particular, there has been much critique of the impact of REDD+ on local forest communities, and whether these interventions serve to entrench or address existing inequalities and the structural causes of poverty. Taking Ghana's REDD+ process as a case study, McDermott et al.'s (2013) ‘equity framework’ is used to systematically examine the contextual, procedural and distributive dimensions of equity, based on fieldwork carried out from July 2014 to March 2016. br This study draws on stakeholder perspectives and document analysis to draw conclusions about the equity of Ghana's REDD+ process. Our study shows that Ghana's national REDD+ strategy, legal texts and documents aim to ensure that all actors, including local forest communities, are considered ‘subjects of equity’. However, according to stakeholder perspectives and general forest laws and policies, there are multiple barriers to realizing the intended goals of equity. Firstly, the complex, multiple and unclear tenurial arrangements inhibit distributive equity. Secondly, uneven stakeholder knowledge and capacity hamper effective engagement in decision-making and limit procedural equity. Thirdly, contextual factors that are remnants of colonial structures and systems, and that serve competing political and economic interests through resource exploitation impact distributive equity. The ‘equity framework’ reveals that historical contextual factors impact the achievement of equity through REDD+, even with right government policies and strategies in place.